2018
DOI: 10.1039/c8ra00464a
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular hydrogels encapsulating bioengineered mesenchymal stem cells for ischemic therapy

Abstract: We developed supramolecular hyaluronate (HA) hydrogels to encapsulate genetically engineered mesenchymal stem cells (MSCs) for the treatment of limb ischemia. In vivo angiogenic factors could be produced stably by the bioengineered MSCs (BMSCs) within the supramolecular hydrogels showing effective vascular repair and enhanced blood perfusion.Clinical limb ischemia (CLI) is the severe manifestation of peripheral arterial disease, which is one of the most common diseases in the population over 70 years old, up t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Especially, supramolecular HA hydrogels prepared by mixing diaminohexane-conjugated HA (DAH-HA) and CB[6]-conjugated HA (CB[6]-HA) have been extensively investigated for the delivery of bioengineered stem cells (Figure a). The hydrogels have been first exploited as a platform scaffold to deliver fibroblasts and mesenchymal stem cells (MSCs) for tissue engineering applications (Figure b). , After demonstrating the feasibility of the hydrogel system as a 3D scaffold, MSCs genetically engineered to secrete therapeutic proteins were entrapped into the hydrogels and applied to treat target diseases. Bioengineered MSCs to produce mutant interleukin-12 (IL-12M) delivered by the CB[6]/DAH-HA hydrogels showed a significant therapeutic effect on treating cancer (Figure c) .…”
Section: Ha-based Medicinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially, supramolecular HA hydrogels prepared by mixing diaminohexane-conjugated HA (DAH-HA) and CB[6]-conjugated HA (CB[6]-HA) have been extensively investigated for the delivery of bioengineered stem cells (Figure a). The hydrogels have been first exploited as a platform scaffold to deliver fibroblasts and mesenchymal stem cells (MSCs) for tissue engineering applications (Figure b). , After demonstrating the feasibility of the hydrogel system as a 3D scaffold, MSCs genetically engineered to secrete therapeutic proteins were entrapped into the hydrogels and applied to treat target diseases. Bioengineered MSCs to produce mutant interleukin-12 (IL-12M) delivered by the CB[6]/DAH-HA hydrogels showed a significant therapeutic effect on treating cancer (Figure c) .…”
Section: Ha-based Medicinesmentioning
confidence: 99%
“…Bioengineered MSCs to produce mutant interleukin-12 (IL-12M) delivered by the CB[6]/DAH-HA hydrogels showed a significant therapeutic effect on treating cancer (Figure c) . Furthermore, MSCs bioengineered to secrete vascular endothelial growth factor A (VEGF-A) and hepatocyte growth factor (HGF) delivered by the CB[6]/DAH-HA hydrogels promoted vascular repair and enhanced blood perfusion in hind-limb ischemia model mice (Figure d) …”
Section: Ha-based Medicinesmentioning
confidence: 99%
“…The result pointed out that the bioactivity of VEGF and HGF still maintained after released from SAPs hydrogel. Additionally, the synergistic angiogenic effect of VEGF and HGF suggested that HGF might enhance endogenous VEGF expression and co-regulate their pathways during endothelial morphogenesis 41, 42.…”
Section: Discussionmentioning
confidence: 99%
“…To overcome such limitations, Kim's group suggested novel supramolecular hydrogel assemblies based on hyaluronic acid modified with pumpkin‐shaped cucurbit[6]uril (CB[6]) or diaminohexane groups . The highly selective and strong CB[6]–diaminohexane interaction allowed cell encapsulation on self‐assembled hydrogels, which could then be later modularly modified by treating the hydrogel with multifunctional tags‐CB[6], which included RGD domains to promote cell adhesion, FITC probes for in vivo detection, or TGF‐β3 and dexamethasone to regulate mesenchymal stem cells' chondrogenic differentiation . Other interesting systems can comprise dock‐and‐lock (DnL) mechanisms based on engineered proteins and anchoring proteins attached to multiarm crosslinker polymers, which can instantly lock onto recombinant “docking” domains under physiological conditions .…”
Section: Cell–biomaterials Assembliesmentioning
confidence: 99%